EFFORTS TO IMPROVE STUDENTS’ INTEREST IN LEARNING MATHEMATICS THROUGH THE INTEGRATION OF THE PANCASILA STUDENT PROFILE PROJECT (P5) AT SMP NEGERI 21 KOTA BEKASI - Abidin, Zainal; Rugaiyah, Rugaiyah; Ahmad, Masduki (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2025)
This study aims to explore the implementation of Classroom Action Research (CAR) as a professional development strategy for teachers across various areas of educational services at SMP Negeri 21 Kota Bekasi. Using a descriptive qualitative approach with a case study design, the research involved teachers as the primary subjects, with school principals and students as supporting data sources. Data were collected through observation, interviews, questionnaires, and documentation, and analyzed using the Miles & Huberman model. The findings indicate that CAR enhances teachers' pedagogical, professional, social, and personal competencies. Furthermore, it strengthens educational services such as academic instruction, counseling, and classroom management. The study also reveals several structural and cultural challenges, which can be addressed through school management support and a collaborative culture. CAR is proven to be an effective reflective strategy for improving the quality of learning while empowering teachers as facilitators of change in the classroom.